Cowboy Boyd and mighty Calliope - Moser, Lisa (Random House, 2013)
A cowboy and his trusty rhinocerous try to prove themselves at the Double R Ranch, where the Slim, Hardtack, and Rancher Rose doubt Calliope's potential, but Boyd believes in her.